Weights Estimation by Firefly with Predation Optimization for Ensemble Precipitation Prediction Using Brams - Luz, Eduardo da; Santos, Ariane dos; Becceneri, José; Velho, Haroldo de Campos; Freitas, Saulo; Gan, Manoel; Mattos, João de; Grell, Georg (Ciência e Natura, 2013)
Uma média ponderada usando diferentes esquemas de convecção pode ser usada em previsão. O problema inverso de estimação de parâmetros é formulado pela a diferença quadrática entre a precipitação medida e a calculada. A função objetivo é minimizada pelo Algoritmo Firefly com Predação. O método é aplicado ao código BRAMS. The precipitation prediction is addressed by weighted average. The weight identification Is a parameter estimation inverse problem formulated by the square difference between measurements and computed precipitations. The metaheuristic Firefly Algorithm with Predation (FAP) is used to compute the best weights. The method is applied to the BRAMS code.